Review on Waqf in Ottoman - Sherrindra Avedta (Islamic Economics and History, 2023)
The waqf system is a welfare system implemented in Islam. In this case, the waqf system has made it easier for the State to run government, as well as providing positive value for its people. The Ottoman government or Ottoman Türkiye organized the management of waqf for the interests and welfare of its people. The government forms a waqf body that takes care of collecting and managing waqf. This research aims to determine the development of waqf in the Ottoman Empire, published by leading journals on Islamic economics. The data analyzed consisted of 72 indexed research publications. The data was then processed and analyzed using the VoSviewer application to find out a bibliometric map of the development of waqf research in Ottoman. The results show that the keywords most frequently used in studies on the theme of Waqf in Ottoman are Waqf, history, human, and Eurasia.